Pengaruh Literasi Keuangan dan Digital Payment Terhadap Kinerja UMKM Kota Tomohon - Purba, Pebisitona Mesajaya; Sumiok, Cristofer; Marunduh, Andrew Patrick (MEASUREMENT : Jurnal Program Studi Akuntansi, 2025)
This study aims to analyze the effect of financial literacy and digital payment on the performance of Micro, Small and Medium Enterprises (MSMEs) in Tomohon City. Using a quantitative approach with the type of explanatory research, this study involved respondents of MSME actors who were taken through proportional stratified random sampling techniques. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software version 4.0. The results showed that financial literacy has a positive and significant effect on MSME performance, indicating that increasing the understanding and ability of MSME actors in managing the financial aspects of the business is a crucial factor in improving business performance. MSME players with good financial literacy show superior ability to manage cash flow, conduct strategic business planning, and make the right investment decisions. In contrast, digital payment does not show a significant effect on MSME performance, although the direction of the relationship shows a positive trend. The findings provide important implications that financial literacy improvement programs need to be prioritized in the development of MSMEs, while the adoption of digital payment technology requires a more holistic approach by considering supporting factors such as technological infrastructure, digital literacy, and local market characteristics.